1970
DOI: 10.21273/jashs.95.6.827
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Factors Influencing Fruit Size in Large-Fruited and Small-Fruited Clones of Strawberry1

Abstract: The relative decline in fruit size from primary to secondary to tertiary positions on the inflorescence of large-fruited clones was much greater than for small-fruited clones. Large-fruited clones produced fruit with more achenes and larger achenes than did small-fruited clones. Fruit weight was positively correlated with total achenes per fruit, developed achenes per fruit, mean weight of total and developed achenes, and fruit weight per developed achene. These results lead to the conclusion that fruit size d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1985
1985
2012
2012

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…Each of these values was the smallest observed for the corresponding genotype grown in the hill system. Thus, the mean number of achenes/cm2 was very high compared to pre- vious studies (2,4,7). This difference probably was due to both genotypic and environmental differences between previous studies and this study.…”
Section: R Esults An D Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Each of these values was the smallest observed for the corresponding genotype grown in the hill system. Thus, the mean number of achenes/cm2 was very high compared to pre- vious studies (2,4,7). This difference probably was due to both genotypic and environmental differences between previous studies and this study.…”
Section: R Esults An D Discussionmentioning
confidence: 56%
“…Thus, in the matted row, genotypic variation in berry weight and, perhaps, yield were more dependent on total number of achenes per berry than the NA/C. Moore et al (4) found that large-fruited clones had more achenes per berry and produced more receptacle tissue per achene than small-fruited clones. However, Olsen et al (7) found that differences in berry weight of two genotypes could not be accounted for by differences in the total number of achenes per berry.…”
Section: R Esults An D Discussionmentioning
confidence: 99%
“…The difference in berry size between 'Benton' and OR-US 4356 cannot be attrib uted to number of achenes/berry, as there was no significant difference either year (Ta ble 2). As others conclude (12), however, fruit size differences among strawberry clones vary not only with achene number but with size of achenes and their differential activity in relation to growth hormones.…”
Section: Literature Citedmentioning
confidence: 82%
“…In areas where temperatures are cool for 2-3 weeks after bloom, apples attain type most regularly (4, 7, 8, 10, 11). Rootstock, strain, crop density, and flower position also affect length/diameter (L/D) ra tios of 'Delicious' fruit (9,12,15). High postbloom temperatures apparently affect the balance of endogenous auxins, gibberellins, and cytokinins, resulting in the cessation of cell division and elongation and ultimately causing flattened fruit (9,12).…”
mentioning
confidence: 99%
See 1 more Smart Citation